GELASTIC SEIZURES - M. B. Mironov; I. V. Ivanova; K. Yu. Mukhin (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: gelastic seizures are focal epileptic seizures that involve sudden outbursts of forced laughter. In our study Gelastic seizures were revealed in 25 patients that comprised 1,98% of all epilepsy events with onset under 18 years of age (n=1261). Male patients prevailed in the group: 16 male patients (64.0%) against 9 female patients (36.0%). Symptomatic focal epilepsy was identified most frequently - in 80% of patients. Cryptogenic focal epilepsy (probably symptomatic focal epilepsy) was defined in 20% of cases. Epilepsy onset varied in a broad age interval: from the first day after birth till 16 years, 4.53+4.52 years on average. Most often (82%) onset was observed in the first years of life - from the first days of life till 6 years old. Clinical findings may disclose 12 different types of seizures. Most frequently were observed: focal motor seizures with typical automatisms - 64% of cases, secondarily generalized tonic-clonic seizures - 48% of cases and tonic seizures - in 32% of all cases. MRI changes: hypothalamic hamartoma - 32% of cases, temporal lobe atrophy - 12% of cases, DNET - 8% of cases, focal cortical dysplasia (insular-opercular region) - 4%, local bifrontal atrophy - 8%, Tuberous Sclerosis - 8% of cases, diffuse cerebral atrophy presented in the form of ventriculomegalia was diagnosed in 2 patients - 8% of cases. Remission was achieved only in 24% of cases. Whereas, in 12% of cases seizures were blocked only after surgical intervention. Reduction of seizures frequency >50% was observed in 20% of patients. In 56% of cases AED therapy produced no significant effect.